2004
DOI: 10.1016/s0002-9440(10)63429-3
|View full text |Cite
|
Sign up to set email alerts
|

ADAM12 Is Selectively Overexpressed in Human Glioblastomas and Is Associated with Glioblastoma Cell Proliferation and Shedding of Heparin-Binding Epidermal Growth Factor

Abstract: ADAMs (a disintegrin and metalloproteinases) are multifunctional molecules involved in cell-cell fusion, cell adhesion, membrane protein shedding, and proteolysis. In the present study, we examined the mRNA expression of 13 different ADAM species with putative metalloproteinase activity in human astrocytic tumors, nonneoplastic brain tissues, and other intracranial tumors by reverse transcriptase-polymerase chain reaction, and found that prototype membrane-anchored ADAM12 (ADAM12m) is predominantly expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
119
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(129 citation statements)
references
References 36 publications
8
119
1
1
Order By: Relevance
“…Because ADAM-12 is synthesized at a high level in several cancers (5,(10)(11)(12)(13)(14)(15), it is tempting to speculate that alteration of Z-DNAmediated transcriptional regulation of ADAM-12 might be responsible, at least in part, for such an increase. Further understanding of the molecular basis of ADAM-12 regulation will have functional implications for suppressing ADAM-12 linked pathologies and ultimately lead to design of new therapeutics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because ADAM-12 is synthesized at a high level in several cancers (5,(10)(11)(12)(13)(14)(15), it is tempting to speculate that alteration of Z-DNAmediated transcriptional regulation of ADAM-12 might be responsible, at least in part, for such an increase. Further understanding of the molecular basis of ADAM-12 regulation will have functional implications for suppressing ADAM-12 linked pathologies and ultimately lead to design of new therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…9. In many tumor tissues, including breast, liver, gastric, brain, bone, and prostate cancer, ADAM-12 mRNA level is increased (10)(11)(12)(13)(14)(15). ADAM-12 is being considered as a marker of breast cancer progression (5) and prostate tumor progression (15).…”
mentioning
confidence: 99%
“…Similarly, angiogenesis (also essential to tumour progression) is reliant on the positive and negative regulation of proteases such as the MMPs, ADAMs and ADAMTS (review by Handsley and Edwards, 2005). Until recently, the ADAMs and ADAMTS genes were relatively understudied in brain tumours (and other cancers), however, recent reports have suggested roles for ADAMTS-4, TS-5 (HeldFeindt et al, 2006;Nakada et al, 2005) and ADAM-12 (Kodama et al, 2004) in GBM, where these proteases are overexpressed. In contrast, we have shown that the expression of ADAMTS-8 is downregulated in brain tumours relative to normal brain.…”
Section: Discussionmentioning
confidence: 99%
“…The membrane-bound ADAM-12 variant is overexpressed in glioblastomas [123] and a treatment of cultured glioblastoma cells with an ADAM-12 inhibitor decreases the production of mature HB-EGF indicating that ADAM-12-HB-EGF pathway might be of biological significance in those cells.…”
Section: Brain Tumoursmentioning
confidence: 99%